Pathogenicity of local isolates of Erysipelothrix rhusiopathiae serotypes 1, 2, 6, ! 1, 12, and type N in mice and pigs - Siti Chotiah (Indonesian Center for Animal Research and Development (ICARD), 1998)
Six local isolates of Erysipelothrix rhusiopathiae of serotypes 1, 2, 6, 11, 12 ; ?,.;d type N isolated from the tonsil of healthy pigs at Kapuk, Jakarta, slaughter house were examined for their pathgb-;ucity for mice and pigs . Forty-two groups of mice, each contains ten mice and twenty-one pigs divided into seven groups were used as experimental animals. Isolates of serotype 1, 2, 6, 11, 12, and type N were pathogen for rnil.e with LDSO of 10